The Impact of Digital Export Systems on Reducing National Logistics Costs - Yusi Rahmawati; Tini Utami; Iik Suryati Azizah; Haris Padilah (Politeknik bumi Akpelni, 2026)
This study aims to analyze the impact of digital export systems on reducing national logistics costs in Indonesia. Although Indonesia’s export volume continues to rise, its logistics costs remain relatively high, largely due to inefficient administrative and coordination processes. The implementation of digital systems such as the Indonesia National Single Window (INSW), Electronic Bill of Lading (e-BL), and Terminal Operating System (TOS) is intended to enhance transparency, accelerate service procedures, and minimize reliance on manual documentation. This research employs a qualitative descriptive approach, with data collected through in-depth interviews, on-site observations at the port, and document analysis related to export procedures. The findings indicate that digital export systems contribute to shorter processing times, improved data accuracy, and reduced operational expenses. However, the effectiveness of these systems is still influenced by human resource readiness and inter-agency system integration. Therefore, digital export transformation has the potential to strengthen Indonesia’s international trade competitiveness, although it requires further enhancement of user capabilities and cross-sector policy alignment.